MOCVD ZnO/Screen Printed Ag Back Reflector for Flexible Thin Film Silicon Solar Cell Application - Amornrat Limmanee; Patipan Krudtad; Sasiwimon Songtrai; Suttinan Jaroensathainchok; Taweewat Krajangsang; Jaran Sritharathikhun; Kobsak Sriprapha (International Journal of Photoenergy)
We have prepared Ag back electrode by screen printing technique and developed MOCVD ZnO/screen printed Ag back reflector for flexible thin film silicon solar cell application. A discontinuity and poor contact interface between the MOCVD ZnO and screen printed Ag layers caused poor open circuit voltage (Voc) and low fill factor (FF); however, an insertion of a thin sputtered ZnO layer at the interface could solve this problem. The n type hydrogenated amorphous silicon (a-Si:H) film is preferable for the deposition on the surface of MOCVD ZnO film rather than the microcrystalline film due to its less sensitivity to textured surface, and this allowed an improvement in the FF. The n-i-p flexible amorphous silicon solar cell using the MOCVD ZnO/screen printed Ag back reflector showed an initial efficiency of 6.2% with Voc=0.86 V, Jsc=12.4 mA/cm2, and FF = 0.58 (1 cm2). The identical quantum efficiency and comparable performance to the cells using conventional sputtered Ag back electrode have verified the potential of the MOCVD ZnO/screen printed Ag back reflector and possible opportunity to use the screen printed Ag thick film for flexible thin film silicon solar cells.